‘Third wave feminism has led us to want to be EVERYTHING, amazing mothers, incredible professionals, perfect partners’: British Female Academics and the Politics of Reproduction - Rebecca Buchanan (Janeway JS, 2018)
This exploratory ethnography investigates the everyday lives of British female academics at home and at work to ascertain to what extent they resonate with the feminist critique of the politics of reproduction. Purposeful sampling identified three respondents with a range of experiences and data including auto-ethography was gathered via a short questionnaire. With deductive analysis this was compared with historical and contemporary feminist analysis. The main topics covered include: (1) Reproductive Choices, (2) Marxism and the Second Shift, (3) Biomedical Bias, (4) Binaries in Relationships and the Male Role, (5) Individualism and the Child's Point of View. The data indicates variability in progress on these issues after more than a century of feminist campaigning. Indeed, increased oppurtunities have materialised as increased pressure as the women aspire to achieve in every area of their lives within an unsupportive culture and an austerity focussed economic policy. The examination leads to a celebration of the individual creative responses to patriarchal restrictions and a recommendation for men to voluntarily make greater efforts towards equality.
Keywords: archive; canon; influence; women' s writing